Epidemiological characteristics and molecular evolution mechanisms of carbapenem-resistant hypervirulent Klebsiella pneumoniae - Han, Yu-Ling; Wen, Xu-Hui; Zhao, Wen; Cao, Xi-Shan; Wen, Jian-Xun; Wang, Jun-Rui; Hu, Zhi-De; Zheng, Wen-Qi (Frontiers in Microbiology, 2022)
Carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-hvKP), a type of Klebsiella pneumoniae (KP) that exhibits hypervirulence and carbapenem resistance phenotypes, can cause severe infections, both hospital- and community-acquired infections. CR-hvKP has brought great challenges to global public health and is associated with significant morbidity and mortality. There are many mechanisms responsible for the evolution of the hypervirulence and carbapenem resistance phenotypes, such as the horizontal transfer of the plasmid carrying the carbapenem resistance gene to hypervirulent Klebsiella pneumoniae (hvKP) or carbapenemase-producing Klebsiella pneumoniae (CRKP) acquiring a hypervirulence plasmid carrying a virulence-encoding gene. Notably, KP can evolve into CR-hvKP by acquiring a hybrid plasmid carrying both the carbapenem resistance and hypervirulence genes. In this review, we summarize the evolutionary mechanisms of resistance and plasmid-borne virulence as well as the prevalence of CR-hvKP.